PERSEPSI PENGUNJUNG TERHADAP POTENSI DAYA TARIK WISATA CAMP LEAKEY DI TAMAN NASIONAL TANJUNG PUTING - Roslinda, Emi; Sabathino, Pedro; Muin, Sudirman (Universitas Tanjungpura, 2023)
Camp Leakey is a tourist attraction in the Tanjung Puting National Park (TNTP) area and has many potential tourist attractions. This research aims to describe visitor's perception of the potential tourist attraction Camp Leakey in TNTP. The research method used was a survey method of 92 respondents who were determined using accidental sampling. Data collection techniques in the form of observation and questionnaires. Analysis of research data using quantitative descriptive. The results of the study showed that visitor's perceptions of potential tourist attraction Camp Leakey were based on each indicator, namely: (1) The attraction component is in the Very Good category with an average value of 399 and a percentage of (86,73%). (2) The accessibility component is in the Very Good category with an average value of 387 and a percentage of (84,13%). (3) The amenity component is in a good category with an average value of 357 and a percentage of (77,60%). (4) The ancillary services component is in the Very Good category with an average value of 396 and a percentage of (86,08%). Overall, the value of visitor's perception of potential tourist attraction Camp Leakey is 385 and has a percentage of (83.69%) which means that the potential tourist attraction Camp Leakey is